2023
DOI: 10.1039/d2fo02946d
|View full text |Cite
|
Sign up to set email alerts
|

Binding of ankaflavin with bovine serum albumin (BSA) in the presence of carrageenan and protective effects of Monascus yellow pigments against oxidative damage to BSA after forming a complex with carrageenan

Abstract: Ankaflavin (AK) is the typical yellow pigment extracted from Monascus-fermented rice with several biological effects, while its solubility is poor. Thus, researches about the delivery systems of AK, especially those...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…As seen in Table 2, the values of ∆G 0 were negative, demonstrating the spontaneity of the binding of AK/MS to α-Glu. Following the rules described by Ross and Subramanian, ∆S 0 > 0 and ∆H 0 < 0 indicated that hydrogen bonds and hydrophobic interactions dominantly contributed to the formation and stabilization of the α-Glu-AK/MS complexes [34,35]. Moreover, ∆H 0 < 0 implied that the binding of AK/MS to α-Glu was an exothermic process.…”
Section: Binding Constants and Thermodynamic Parametersmentioning
confidence: 84%
“…As seen in Table 2, the values of ∆G 0 were negative, demonstrating the spontaneity of the binding of AK/MS to α-Glu. Following the rules described by Ross and Subramanian, ∆S 0 > 0 and ∆H 0 < 0 indicated that hydrogen bonds and hydrophobic interactions dominantly contributed to the formation and stabilization of the α-Glu-AK/MS complexes [34,35]. Moreover, ∆H 0 < 0 implied that the binding of AK/MS to α-Glu was an exothermic process.…”
Section: Binding Constants and Thermodynamic Parametersmentioning
confidence: 84%
“…In 2022, Hoseyni et al [49] explored the interaction between ten synthetic food dyes (Quinoline Yellow, Sunset Yellow, Carmoisine, Amaranth, Red 2G, Allura Red AC, Patent Blue V, Brilliant Blue FCF, Food Green S and Fast Green) and HSA through fluorescence spectroscopy, bio-partitioning micellar chromatography (BMC), and molecular docking analyses. The findings from fluorescence spectroscopy revealed a pronounced quenching effect on the intrinsic fluorescence of HSA, indicating a strong interaction near the Trp-214 residue of HSA.…”
Section: Potential Findings and Latest Applications Of Serum Protein ...mentioning
confidence: 99%
“…A model was developed to assess the relationship between BMC retention data and the K b of food dyes, and the predictive capability of the model was evaluated. Moreover, molecular docking studies indicated that synthetic food dyes have the potential to bind within the extensive hydrophobic cavity of site I (subdomain IIA) in HSA [49].…”
Section: Potential Findings and Latest Applications Of Serum Protein ...mentioning
confidence: 99%